Probing Co- and Fe-doped LaMO3 (M = Ga, Al) perovskites as thermal sensors. Issue 2 (8th December 2017) - Toulemonde, Olivier; Devoti, Alexis; Rosa, Patrick; Guionneau, Philippe; Duttine, Mathieu; Wattiaux, Alain; Lebraud, Eric; Penin, Nicolas; Decourt, Rodolphe; Fargues, Alexandre; Buffière, Sonia; Demourgues, Alain; et al.
Abstract : Spin crossover phenomenon in Co-doped La(Al/Ga)O3 compounds with the perovskite structure is shown to be useful as thermal sensors. Abstract : The synthesis of a Co-doped or Fe-doped La(Ga, Al)O3 perovskite via the Pechini process aimed to achieve a color change induced by temperature and associated with spin crossover (SCO). In Fe-doped samples, iron was shown to be in the high-spin state, whereas SCO from the low-spin to the high-spin configuration was detected in Co-doped compounds when the temperature increased. Fe-doped compounds clearly adopted the high-spin configuration even down to 4 K on the basis of Mössbauer spectroscopic analysis. The original SCO phenomenon in the Co-doped compounds LaGa1− x Co x O3 (0 < x < 0.1) was evidenced and discussed on the basis of in situ X-ray diffraction analysis and UV-vis spectroscopy. This SCO is progressive as a function of temperature and occurs over a broad range of temperatures between roughly 300 °C and 600 °C. The determination of a crystal field strength of about 2 eV and a Racah parameter B of about 500 cm −1 for Co 3+ (3d 6 ) ions show that these values allow the occurrence of SCO. Hence, this study shows the possibility of using LaGa1− x Co x O3 compounds as thermal sensors at low Co contents ( x = 0.02). The competition between steric and electronic effects in LaGaO3 in which Co 3+ is stabilized in the LS state shows that electronic effects with the creation of M–O covalent bonds are predominant and contribute to the stabilization of a high crystal field around Co 3+ (LS) although its ionic radius is smaller in comparison with that of Ga 3+ .